Innenrücktitelbild: Binuclear Copper(I) Complexes for Near‐Infrared Light‐Emitting Electrochemical Cells (Angew. Chem. 38/2023) - Jouaiti, Abdelaziz; Ballerini, Lavinia; Shen, Hsiang‐Ling; Viel, Ronan; Polo, Federico; Kyritsakas, Nathalie; Haacke, Stefan; Huang, Yu‐Ting; Lu, Chin‐Wei; Gourlaouen, Christophe; Su, Hai‐Ching; Mauro, Matteo (Angewandte Chemie, 2023)
Near‐infrared light‐emitting electrochemical cells (LECs) are appealing optoelectronic devices with potential application in low‐cost, large‐area display technology and disposable devices for telecommunication, night‐vision displays and phototherapeutics. Bimetallic copper(I) complexes were synthetized and investigated by Abdelaziz Jouaiti, Hai‐Ching Su, Matteo Mauro et al. in their Research Article (e202305569). These earth‐abundant compounds were demonstrated as suitable emitters for solution‐processed LECs with electroluminescence into the NIR region.